ChemInform Abstract: Oxidative Trifluoromethylation of Unactivated Olefins: An Efficient and Practical Synthesis of α‐Trifluoromethyl‐Substituted Ketones. Issue 7 (18th February 2014) - Deb, Arghya; Manna, Srimanta; Modak, Atanu; Patra, Tuhin; Maity, Soham; Maiti, Debabrata
Abstract An efficient and general method to access α‐CF3‐substituted ketones is developed.